Translational potential of human embryonic and induced pluripotent stem cells for myocardial repair: Insights from experimental models - Kong, Chi-Wing; Akar, Fadi G.; Li, Ronald A. (Thrombosis and Haemostasis, 2010)
Heart diseases have been a major cause of death worldwide, including developed countries. Indeed, loss of non-regenerative, terminally differentiated cardiomyocytes (CMs) due to aging or diseases is irreversible. Current therapeutic regimes are palliative in nature, and in the case of end-stage heart failure, transplantation remains the last resort. However, this option is significantly hampered by a severe shortage of donor cells and organs. Human embryonic stem cells (hESCs) can self-renew while maintaining their pluripotency to differentiate into all cell types. More recently, direct reprogramming of adult somatic cells to become pluripotent hES-like cells (a.k.a. induced pluripotent stem cells or iPSCs) has been achieved. The availability of hESCs and iPSCs, and their successful differentiation into genuine human heart cells have enabled researchers to gain novel insights into the early development of the human heart as well as to pursue the revolutionary paradigm of heart regeneration. Here we review our current knowledge of hESC-/iPSC-derived CMs in the context of two fundamental operating principles of CMs (i.e. electrophysiology and Ca2+-handling), the resultant limitations and potential solutions in relation to their translation into clinical (bioartificial pacemaker, myocardial repair) and other applications (e.g. as models for human heart disease and cardiotoxicity screening).
Keywords: Human embryonic stem cells; cardiomyocytes; induced pluripotent stem cells